2022
DOI: 10.15252/embr.202254992
|View full text |Cite
|
Sign up to set email alerts
|

Birth of mice from meiotically arrested spermatocytes following biparental meiosis in halved oocytes

Abstract: Microinjection of spermatozoa or spermatids into oocytes is a major choice for infertility treatment. However, the use of premeiotic spermatocytes has never been considered because of its technical problems. Here, we show that the efficiency of spermatocyte injection in mice can be improved greatly by reducing the size of the recipient oocytes. Live imaging showed that the underlying mechanism involves reduced premature separation of the spermatocyte's meiotic chromosomes, which produced much greater (19% vs. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In human oocytes, chromosomal misalignment due to unstable spindle bipolarity does not block anaphase onset through the spindle checkpoint [ 99 ]. A recent study showed that the efficiency of spermatocyte injection in mice could be greatly improved by reducing the size of recipient oocytes [ 100 ]. In this study, spermatocyte chromosomes, which might be intrinsically more error-prone, were dramatically rescued from segregation error by reducing the cytoplasm.…”
Section: Chromosome Segregation Error Due To Large Cytoplasmic Size O...mentioning
confidence: 99%
“…In human oocytes, chromosomal misalignment due to unstable spindle bipolarity does not block anaphase onset through the spindle checkpoint [ 99 ]. A recent study showed that the efficiency of spermatocyte injection in mice could be greatly improved by reducing the size of recipient oocytes [ 100 ]. In this study, spermatocyte chromosomes, which might be intrinsically more error-prone, were dramatically rescued from segregation error by reducing the cytoplasm.…”
Section: Chromosome Segregation Error Due To Large Cytoplasmic Size O...mentioning
confidence: 99%
“…A study by Ogonuki et al ( 2022 ) of EMBO Reports deals with a different in vitro fertilization method in mouse oocytes: injection of diploid sperm nuclei before they undergo the first meiotic division, into equally diploid, GV‐stage oocytes. The logic behind this approach is that the oocyte cytoplasm should be able to support the meiotic divisions not only of female, but also of male chromosomes, should they be present (i.e., biparental meiosis).…”
mentioning
confidence: 99%